Mahatma Gandhi and Prema Kantak : exploring a relationship, exploring history (O. U. P, 2013)
An important feminist thinker, writer, and activist, Prema Kantak's contributions to Indian feminist thought and the nationalist movement have been largely neglected in scholarly studies. Kantak, a one-time resident of Gandhi's ashram, forged a special, life-long bond with the Mahatma, and was hugely influenced by his thought and persona. She rose to prominence as a feminist writer with strong, radical convictions and also as a forceful proponent of Gandhian political and social ideals in Maharashtra.